Nudge, Embarrassment, and Restriction-Replies to Voigt, Tieffenbach, and Saghai - Nir Eyal (Kerman University of Medical Sciences, 2015)
It is a privilege that some of the most promising contributors to public health ethics took the time to think and comment on my op-ed. Kristin Voigt's (1), Emma Tieffenbach's (2), and Yashar Saghai's (3) ingenious comments have taught me a lot about nudging, embarrassment, and restriction. Let me address their main points one by one.